Does educational inequality lead to income inequality? Evidence from Pakistan - Cheema, Ahmed Raza; Ghaffar, Shanza; Ul-Haq, Jabbar; Hye, Qazi Muhammad Adnan (Edelweiss Applied Science and Technology, 2023)
One of the main issues that developing nations like Pakistan are dealing with is income inequality. Education, inter Alia, plays a key role in reducing income inequality. Theoretically, in developing countries, it is anticipated that there exist two groups: the bourgeoisie (have) and the proletariat (have not), as suggested by Karl Marx, and there is an educational difference between these two groups, and Pakistan is no exception. This study aims to investigate the impact of educational inequality on income inequality at the provincial level of Pakistan with a rural-urban break up for the period from 1998-99 to 2018-19 (pooled data). Keeping in view the nature of the data, panel data techniques are applied. Appropriate tests (i.e., the F-test and the Hausman Specification test) suggest that Fixed Effect Model is the preferred model. The results show that there is a statistically significant positive link between educational inequality and income inequality. The results are robust to various proxies of educational inequality and income inequality (i.e., Gini coefficient, Generalized Entropy, and Atkinson Index) as well as to control variables (i.e., income and poverty). Further, the study found the negative relation between income and income inequality to be statistically significant, indicating that an increase in income leads to a decrease in income inequality. Moreover, the impact of poverty on income inequality is positive and statistically significant. The policy insinuation is that the government should focus on reducing educational inequality to reduce income inequality in Pakistan.